Evaluation of hepatocyte-derived microRNA-122(miR-122) For diagnosis of selected hepatobiliary diseases of dogs - Eman Shawky Ramadan Mahmoud; Faisal A. Torad; Shaymaa I. Salem; Taher A. Baraka (Cairo : Eman Shawky Ramadan Mahmoud, 2019)
Hepatobiliary diseases are commonly encountered in canine medicine and can be classified into parenchymal, vascular, biliary or neoplastic diseases. Diagnosis of liver diseases is considered a chal(S1(Blenge for a veterinarian and requires a lot of diagnostic workup as specific clinical signs become overt only when hepatocellular damage became massive so new sensitive, non invasive hepatic diagnostic biomarkers are needed. In this study 64 dogs were used, 15 of them were used as a normal control group, 10 of them were used for induction of steroid hepatopathy and 39 of them suffered from hepatobiliary diseases. Diagnostic workup were recorded including clinical examination, hematology, serum biochemical constituents, abdominal ultrasonography, US guided fine-needle liver biopsy for cytological and histopathological investigations and serum hepatocyte derived miRNA-122 analyzed by real-time quantitative polymerase chain reaction. In conclusion, serum hepatocyte derived miRNA-122 is of diagnostic value and highly stable, non invasive, easily measurable blood indicator for detection of hepatocellular injury in dogs in addition to miRNA-122 highly significant elevated in acute hepatitis, chronic hepatitis, canine multicentric lymphoma involving liver, slightly elevated in steroid induced hepatopathy and moderate elevated in biliary diseasess
Thesis (Ph.D.) - Cairo University - Faculty of Veterinary Medicine - Department of Internal Medicine and Infectious Diseases
Issued also as CD
Keywords: Canine; Hemato-biochemical analysis; Hepatobiliary diseases